HIV treatment cascade among transgender women in a San Francisco respondent driven sampling study. (8th April 2014) - Santos, Glenn-Milo; Wilson, Erin C; Rapues, Jenna; Macias, Oscar; Packer, Tracey; Raymond, H Fisher
Abstract : Objective: Male-to-female transgender women (transwomen) have a disproportionate burden of HIV. We sought to estimate HIV treatment cascade indicators among transwomen in San Francisco. Methods: We conducted a respondent driven sampling (RDS) study of 314 transwomen from August to December 2010. The study tested participants for HIV and collected self-reported data on linkage and access to care, viral load and antiretroviral treatment (ART). We derived population-based estimates and 95% CIs of cascade indicators using sampling weights based on established RDS methods. We conducted RDS-weighted logistic regression analyses to evaluate correlates of being on ART and being virologically suppressed (viral load ≤200 copies/mL). Results: The RDS-weighted population-based estimate of HIV prevalence was 39% (95% CI 32% to 48%) among transwomen tested for HIV. Among HIV-positive transwomen, 77% (95% CI 70% to 93%) reported being linked to care within 3 months of diagnosis and 87% (95% CI 76% to 98%) accessed care in the past 6 months. In addition, 65% (95% CI 54% to 75%) were on ART, and less than half (44%; 95% CI 21% to 58%) were virologically suppressed. Housing instability was associated with lower odds of being on ART and being virologically suppressed. Conclusions: We observed a high prevalence of HIV in our population-based estimates of transwomen in San Francisco, coupled with modest ART use and low virological suppression rates, indicating high potential for forward transmission. Poor HIV treatment outcomes were consistently associated with housing instability. These data suggest that multi-level efforts, including efforts to address housing insecurity, are urgently needed to ameliorate disparities in HIV clinical outcomes among transwomen and reduce secondary HIV transmission to their partners.